IMPLEMENTASI PENATAAN DAN PEMBINAAN PUSAT PERBELANJAAN DAN TOKO SWALAYAN OLEH DINAS PERDAGANGAN KOPERASI DAN USAHA MIKRO KABUPATEN PONOROGO - Niswandri Prasojo, Andri; Nurati, Dian Esti; Purwanto, Adi (Master of Public Administration, Universitas Slamet Riyadi, 2020)
This study aims to describe and analyze how the implementation of structuringand guiding shopping centers and convenience stores by Trade Cooperatives andMicro Enterprises office of Ponorogo Regency along with what are the supportingfactors and obstacles to its implementation. This type of research is qualitativeresearch using the theory of George C. Edward III as a basis for thinking inassessing the implementation of policies that are influenced by 4 main variablesnamely communication, resources, disposition, and bureaucratic structure. Themethod of data collection is done by observation, interviews, and documentation.The results showed that the implementation has not been running optimally.Communication is good enough. Resources are not optimal, the number of staffand supporting facilities for implementation are still inadequate. Disposition, theselection of personnel is appropriate, but there is no incentive. BureaucraticStructure is not optimal yet the absence of Regional Regulations or RegentsRegulations affecting Standard Operating Procedures (SOPs) and fragmentationbetween work units involved in the implementation process.